(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
This article is a discriminating study on the orientalsources which two major poets–W.B. Yeats and T.S. Eliot–exploited for theinvestigation of another focal point of life and another foundation of qualities.They felt powerfully attracted to the heavenly myths of antiquated India andendeavored to join them with those of the West through their interminablecenterpieces. They were affected by eastern considered, however progressivelyas borrowers than as followers, in light of the fact that the temper of theirown reasoning was not eastern. What they gained experience from India wasworked over and reshaped by a feeling of qualities that they accepted haddescended to them through scholars–indian and English. This feeling ofqualities could change their gleanings is theosophy, mystery, Buddhism andmysticism from a hotchpotch to an agreement.